Factors associated with carpal tunnel syndrome among bag craftsmen in Sidoarjo, Indonesia - Farha Kamilatun Noha Fadilah; Nadila Octaria Milenia; Reny Indrayani; Noeroel WIdajati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Carpal Tunnel Syndrome (CTS) is a wrist disorder caused by compression of the median nerve within the carpal tunnel. It commonly manifests as tingling, numbness, and muscle weakness in the fingers or hand. If left untreated, CTS can lead to more severe physical impairment. Workers engaged in repetitive tasks with awkward postures, such as bag craftsmen at UD Sumber Rejeki, are particularly at risk. Purpose: To identify risk factors associated with CTS complaints among bag craftsmen in Sidoarjo Regency. Method: An observational analytic design with a cross-sectional approach was employed. The sample comprised all 43 bag craftsmen. Data were collected through interviews and direct observation using questionnaires, Phalen’s Test sheets, the Boston Carpal Tunnel Questionnaire (BCTQ), and wrist posture evaluations with the RULA method. Bivariate analysis was conducted using Chi-square or Fisher’s Exact tests, with associations expressed as Odds Ratios (OR) and 95% Confidence Intervals (CI). Results were considered significant at p<0.05. Results: CTS complaints were reported by 26 workers (60.5%). Significant associations were found between gender (p=0.045; OR=3.75), length of service (p=0.009; OR=6.81), repetitive movements (p<0.001; OR=19.60), and awkward hand posture (p=0.002; OR=7.11). In contrast, age (p=0.055), smoking history (p=0.206), and medical history (p=0.154) showed no statistically significant associations with CTS complaints. Conclusion: Gender, duration of employment, repetitive movements, and non-ergonomic postures were significantly associated with CTS complaints among bag craftsmen. The industry is encouraged to implement adequate rest breaks and improve workstation ergonomics to reduce the risk of CTS complaints.